Measurement of Hepatocyte Growth Factor, Interleukin 6 and Tumor necrosis factor α in Acute Myocardial Infarction - Keshmiri, Asadallah; Derakhshan, Ali Reza; Fazlinejad, Afsoon; Farid-Hosseini, Reza (Nepalese Heart Journal, 2019)
Background: Early mortality rate due to acute myocardial infarction (AMI) is approximately 30%, and half of these deaths occur before reaching a hospital. The prevention and early detection play a key role in reducing mortality in AMI. Hepatocyte Growth Factor (HGF), Interleukin 6 (IL-6), and Tumor Necrosis Factor α (TNF-α) are most recent prognostic biomarkers for AMI. The present study was aimed to evaluate the level of these cytokines in AMI. Methods: In this case control study, 39 patients with AMI were compared with 30 healthy subjects. Age, sex and other possible confounding factors were matched. AMI diagnosis was confirmed by typical symptoms, electrocardiogram changes and serum concentration of troponin I and creatine kinase-MB. The levels of TNF-α, IL-6 an HGF at baseline and 3 and 7 days later were measured using ELISA method. Results: Levels of IL-6, TNF-α and HGF increased over time after AMI with ST-segment elevation in study group. The baseline IL-6 levels in AMI group were significantly higher than control group (P<0.05). Conclusions: The results of this study suggest that baseline levels of IL-6 as well as serial changes of serum IL-6, TNF-α and HGF concentrations can be used as potential diagnostic biomarkers in AMI.